Clonidine increases bone resorption in humans. Issue 3 (March 2016) - Limonard, E.; Schoenmaker, T.; Vries, T.; Tanck, M.; Heijboer, A.; Endert, E.; Fliers, E.; Everts, V.; Bisschop, P.
Abstract Summary Inhibition of sympathetic signaling to bone reduces bone resorption in rodents. In contrast, we show that pharmacological reduction of the sympathetic tone increases bone resorption in humans in vivo. This effect does not appear to be mediated via a direct pharmacological effect on the osteoclast. Introduction Inhibition of sympathetic signaling to bone reduces bone resorption in rodents. It is uncertain whether a similar role for the sympathetic nervous system exists in humans. The sympathetic tone can be reduced by clonidine, which acts via alpha-2-adrenergic receptors in the brainstem. Our objective was to determine the effect of clonidine on bone turnover in humans. Methods The acute effect of a single oral dose of 0.3 mg clonidine on serum bone turnover markers (C-terminal cross-linking telopeptides of collagen type I (CTx), a marker for bone resorption, and procollagen type 1 N propeptide (P1NP), a marker for bone formation) was determined in a randomized crossover design in 12 healthy volunteers, aged 18–70 years. In addition, we assessed the effect of clonidine on the number of tartrate-resistant acid phosphatase–positive multinucleated cells (TRAcP+ MNCs) and bone resorption. Results CTx concentrations increased after clonidine treatment compared to the control condition (p  = 0.035). P1NP concentrations were not affected by clonidine (p  = 0.520). In vitro, clonidine had no effect on the number of TRAcP+ MNCs (p  = 0.513) or on bone resorption (p  = 0.996). Conclusions We demonstrated that clonidine increases bone resorption in humans in vivo. This effect does not appear to be mediated via a direct effect on the osteoclast.